2018
DOI: 10.3390/ijms19103251
|View full text |Cite
|
Sign up to set email alerts
|

PSMA-Oriented Target Delivery of Novel Anticancer Prodrugs: Design, Synthesis, and Biological Evaluations of Oligopeptide-Camptothecin Conjugates

Abstract: Clinical applications of camptothecin (CPT) have been heavily hindered due to its non-targeted toxicity, active lactone ring instability, and poor water solubility. Targeted drug delivery systems may offer the possibility to overcome the above issues as reported. In this research, a series of prostate-specific membrane antigen (PSMA)-activated CPT prodrugs were designed and synthesized by coupling water-soluble pentapeptide, a PSMA hydrolyzing substrate, to CPT through an appropriate linker. The cytotoxicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The cytotoxicity of 2 – 5 against the two human prostate tumor cell lines PC-3 and LNCaP was determined by the XTT cell viability assay after 48 h of treatment with the test compounds ( Table 1 and Supplementary Material ). LNCaP is known to overexpress the PSMA receptor, whereas PC-3 is receptor-negative [ 29 ]. The thiophene parent drug 2 showed low-micromolar–nanomolar-range activity, with eight times higher activity against PC-3 compared to LNCaP.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of 2 – 5 against the two human prostate tumor cell lines PC-3 and LNCaP was determined by the XTT cell viability assay after 48 h of treatment with the test compounds ( Table 1 and Supplementary Material ). LNCaP is known to overexpress the PSMA receptor, whereas PC-3 is receptor-negative [ 29 ]. The thiophene parent drug 2 showed low-micromolar–nanomolar-range activity, with eight times higher activity against PC-3 compared to LNCaP.…”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of PSMA-activated prodrug CPT-WT-H, the intermediates CPT-A-L 12 and CPT-B-L 12 were synthesized as shown in Scheme S2 according to our previous report. 50 Then, reaction of CPT-B-L 12 with WT-H in the presence of EDCI, N, N-Diisopropylethylamine (DIPEA), and 1-hydroxybenzotriazole (HOBt) in DCM afforded the corresponding intermediate CPT-WT-H-L 12 , which was further treated with TFA to remove the protective groups, yielding the final prodrug CPT-WT-H ( Scheme S2 ). The structure of CPT-WT-H was confirmed by 1 H NMR and 13 C NMR, HRMS and UV absorbance ( Figures S4 – S7 , Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“… 53 , 54 It was reported that structural modifications at the 20-OH of CPT could enhance the stability of the lactone ring. 50 In addition, the formation of stable nanoparticles not only enhanced the aqueous dispersity of CPT but also the stability of the lactone ring. 55 The stability of CPT-WT-H NPs was estimated by DLS and HPLC analysis in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable achievements have also been made in PSA-mediated drug accumulation and efficacy improvement. Concretely, tumor lesions targeted delivery of PSA-specific motif-conjugated nanocomplexes carrying a variety of therapeutics either alone or in combination, mainly included DOX 181 , 182 , 183 , 184 , 185 , PTX 186 , DTX 187 , SN38 188 , camptothecin 189 , thapsigargin 190 , boron-containing reagents 191 , zinc chelator 192 , antibody-drug conjugates 193 , 194 , kinase inhibitors 195 , siRNA ( Fig. 7 ) 196 , 197 , 198 , 199 , 200 , miRNA 201 , oligonucleotide 202 , therapeutic proteins 203 , and chemotherapy-based combination regimens with molecular targeted therapy 204 , antibiotic therapy 205 , gene therapy 206 , 207 , and anti-inflammatory therapy 208 .…”
Section: Protease-responsive Nanodds For the Targeted Theranostics Of Malignancymentioning
confidence: 99%